Trade Unionism and Social Movements: Collective Action and Social Regulation in the European and Portuguese Contexts - Estanque, Elisio (Pontifícia Universidade Católica de São Paulo, 2009)
In this article trade unionism and other social movements are linked, demonstrating their contradictions, but showing their possible or potential complementarities. The struggle for welfare of the working class can give way to forms of rebellion and contestation or even to processes of institutionalization and dialogue. Within this framework of a permanent tension between regulation and emancipation, we discuss some tendencies at work in the long history of modern capitalism, from the 19th century to today, passing through the experiences of the European welfare state.